2009
DOI: 10.1002/jor.20984
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐dependent increases in IL‐1β, substance P, CTGF, and tendinosis in flexor digitorum tendons with upper extremity repetitive strain injury

Abstract: Upper extremity tendinopathies are associated with performance of forceful repetitive tasks. We used our rat model of repetitive strain injury to study changes induced in forelimb flexor digitorum tendons. Rats were trained to perform a high repetition high force (HRHF) handle-pulling task (12 reaches/min at 60 AE 5% maximum pulling force [MPF]), or a low repetition negligible force (LRNF) reaching and food retrieval task (three reaches/min at 5 AE 5% MPF), for 2 h/day in 30 min sessions, 3 days/week for 3-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
156
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(184 citation statements)
references
References 43 publications
21
156
2
Order By: Relevance
“…Past findings demonstrate increased nerve fibers in tissues as a consequence of repetitive tasks (Fedorczyk et al 2010;Kadi et al 1998;Lian et al 2006). SubP is a nociceptor-related neuropeptide (Henry 1982;Jessell 1982) that increases in several painful conditions, including painful tendinopathies, rotator cuff tears, and arthritis (Dean et al 2013;Gotoh et al 1998;Lui et al 2010;Munoz and Covenas 2011;Witonski et al 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Past findings demonstrate increased nerve fibers in tissues as a consequence of repetitive tasks (Fedorczyk et al 2010;Kadi et al 1998;Lian et al 2006). SubP is a nociceptor-related neuropeptide (Henry 1982;Jessell 1982) that increases in several painful conditions, including painful tendinopathies, rotator cuff tears, and arthritis (Dean et al 2013;Gotoh et al 1998;Lui et al 2010;Munoz and Covenas 2011;Witonski et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Adjacent sections of the NC, FRC and 18-week HRHF rat muscles were stained with hematoxylin and eosin (H&E), and with CD11b (a macrophage marker), using previously described methods (Fedorczyk et al 2010;Gao et al 2013). These sections were examined for the presence of neutrophils, lymphocytes or macrophages.…”
Section: Immunohistochemical and Histological Analysesmentioning
confidence: 99%
“…Since we have observed that task-induced tissue inlammation precedes tissue ibrotic responses, including increased CTGF and collagen type 1 production [58][59][60], we next examined the efects of secondary ibuprofen treatment on ibrogenic processes in our rat model [40,61]. In addition to successful reductions of tissue and serum inlammatory responses after ibuprofen treatment, we observed signiicant reductions in TGFB-1 and CTGF protein expression as well as collagen deposition in median nerves ( Figure 3A) and lexor digitorum muscles of 6-week and 12-week HRHF+IBU rats (Figure 6) [40,61].…”
Section: Hrhf Task-induced Tissue Ibrosis Is Efectively Reduced By Ibmentioning
confidence: 99%
“…(K,L) Another stain (a Masson's trichrome stain, which shows collagen as blue) also shows that collagen deposition is increased between myoibers of 6-week HRHF rats compared to NC rats. Used by permission from Abdelmagid et al [60].…”
Section: Hrhf Task-induced Radiocarpal Joint Damage Is Ameliorated Bymentioning
confidence: 99%
“…Comparatively fewer authors have researched MSD biomarkers in younger subjects with incipient disorders (40,41). Animal models would suggest that different biomarkers are present at different MSD stages and may differ by age (87)(88)(89). Various theories of MSD pathophysiology also suggest that differing biochemical biomarkers would occur at different MSD stages (21,82,90).…”
Section: Spectrum Effect (Variation Of Biomarkers Across Subgroups)mentioning
confidence: 99%